Genres of sports media discourse (Eurasian Journal of Philology Science and Education, 2025)
This article aims to study various genres of sports media discourse and their influence on sports culture and perception. The article examines the emotive evaluation of phrases and expressions that were selected from sports discourse materials. The methodological basis of the study is linguistic and comparative analysis, which allows to study the emotive evaluation of phrases from various genres of sports discourse, including news, reports, commentaries, interviews and analytical materials from English-language sources. By analyzing examples from authentic English-language materials and studying the context, the article demonstrates how each genre of sports media discourse performs its unique function: providing relevant information, analyzing strategies and tactics, as well as deep immersion in the world of sports. The article highlights the innovative possibilities of digital technologies in the development of these genres. The results of the comparative analysis help to understand the emotive evaluation of a particular genre of sports discourse. The conclusion emphasizes the importance of critical thinking in perceiving information from various sources of sports media, as well as understanding the emotive coloring of expressions from sources of sports programs. The article contributes to the study of functional varieties of written and oral language of sports media discourse.Keywords: sports media discourse, genres of sports media discourse, sports reportage, sports commentary, emotive evaluation, sports culture, interactive media.